Effects of hydrostatic pressure and temperature on refractive index changes in tuned quantum dots under magnetic field. (1st June 2022) - Chang, Ceng; Li, Xuechao; Duan, Yiming; Zhao, Zhuang; Zhang, Liangcheng
Abstract: The effects of external magnetic field, hydrostatic pressure, temperature and radius of the quantum dots (QDs) on refractive index changes (RICs) of tuned QDs are studied in detail theoretically. In the framework of effective mass approximation, energy levels and wave functions are derived. Simultaneously, the nonlinear RICs are obtained by compact-density-matrix approach and iterative method. Then, the numerical simulations show that under various constraint factors, the resonant peak position of RICs moves to high energy or low energy, that is, blue shift or red shift, and the peak value of RICs will also alter with the change of parameters.